Quality indicators and development targets in the national clinical quality registries in cancer care and screening - Henrik Moller; Søren Paaske Johnsen; Lene Hjerrild Iversen; Anne Gulbech Ording; Amalie Helme Simoni; Lina Marie Vinge Ahlstrøm; Jens Winther Jensen (BMJ Open Quality)
Background The Danish clinical quality registries monitor and improve the quality of care, using quality indicators and defined development targets referred to as ‘standards’. This study aims to investigate the fulfilment of standards in the Danish clinical quality registries in cancer care and screening.Methods Data was included from annual reports in the 27 Danish clinical quality registries in cancer care and screening. The most recent report from each registry was downloaded the 13 December 2023. Indicators were included if: evaluating care or screening over 12 months, presenting a well-defined standard with a desired direction and presenting the proportion and number of individuals for which the standard was fulfilled. Data were extracted on national and regional levels for the last 3 years, and fulfilment of standards was presented as the proportion of indicators that fulfilled the standard within each unit of comparison.Results In total, 216 quality indicators were included. At the national and regional level, standards were fulfilled for 75% and 71%, respectively. Fulfilment within the registries varied from 5% to 100% on national and 12% to 99% on regional level. Standards were more often fulfilled for result (than process indicators) and for established (than supplemental indicators). Altogether, 43% of the standards were fulfilled across all regions delivering data for the specific indicator.Conclusions The approach to defining standards for clinical quality indicators as conservative minimum or ambitious development targets varied in the Danish clinical quality registries in cancer care and screening. This deviating behaviour seriously restrains possibilities for comparing clinical quality across cancers despite the robust infrastructure of the quality registries, limiting the possibilities for overview and prioritising resources and attention to the most urgent cancers.